L−Lysine Amino Acid Adsorption on Zeolite L: a Combined Synchrotron, X‐Ray and Neutron Diffraction Study. Issue 10 (24th September 2020) - Beltrami, Giada; Martucci, Annalisa; Pasti, Luisa; Chenet, Tatiana; Ardit, Matteo; Gigli, Lara; Cescon, Mirco; Suard, Emmanuelle
Abstract: Combined neutron and X‐ray powder diffraction techniques highlighted the sorption capacity of the acidic L zeolite towards the L‐lysine amino acid. The role of zeolite channels in the stabilization of the lysine absorbed and the effect of water on protein structure are elucidated at atomistic level. The stabilization of the L α‐helical conformation is related to strong H‐bonds between the tail aminogroups of lysine molecules and the Brønsted acid site as well as to complex intermolecular H‐bond system between water molecules, zeolite and amino acid. This finding is relevant in the catalytic synthesis of polypeptide, as well as in industrial biotechnology by qualitatively predicting binding behaviour Abstract : The adsorption capacity of the acidic L zeolite towards the L‐lysine was investigated by combining neutron and X‐ray powder diffraction techniques. The stabilization of the L α‐helical conformation is related to strong H−bonds between the tail aminogroups of lysine molecules and the Brønsted acid site as well as to complex intermolecular H‐bond system between water molecules, zeolite and amino acid.